Optimasi Pengiriman Barang menggunakan Algoritme Genetika dengan Data Sintesis - Aulia Dinia; Imam Cholissodin; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Delivery of goods is preparing the delivery of goods from the warehouse to the destination that has been adjusted to the order and delivery documents and in conditions that are in accordance with the requirements for handling the goods. Problems that often occur are the destination locations that are taken have different locations, the goods sent do not reach their destination, couriers who do not understand the delivery route, and lack of determining the distance from one location to another. Therefore, it is necessary to optimize the delivery of goods so that delivery can be carried out more efficiently. One method that can be used to solve this problem is genetic algorithm. Genetic algorithm is a computational method used to select a solution that fits the criteria without having to examine all possible solutions. In this study, a global analysis was carried out by comparing the results of manual calculations with the actual results of the system. Where the manual calculation is the result of deliveries made by JNE without the help of the system. The difference in fitness between the results of manualization of JNE delivery and the results of the system recommendation is 0.007950764. With the results of the recommendation system that gets a fitness of 0.1083108 is better than the results of manualization which produces a fitness of 0.1003060036.